Development of Interactive E-Books for Production Unit Courses by Implementing a Hybrid Learning System - Tampubolon, Hotmaria; Farihah, Farihah; Hanim, Halida; Bahri, Halimul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The purpose of this research is to develop an interactive e-book for production unit courses by applying a valid, practical and effective hybrid learning. The product development model used is the IDI (Instructional Development Institute) model.. The subjects of this study were students of Fashion Design Education. The results obtained from this development research are as follows: (1) The availability of interactive e-books for production unit courses, (2) Production unit interactive e-books are declared to be very valid by material experts (0.86) and media experts ( 0.87), (3) interactive e-books for production unit courses based on lecturer responses are very practical (88%) and based on student responses are stated to be very practical (90%), (4) interactive e-book production units are declared effective in improve student learning outcomes (12.69%). Based on the findings of this study, it was concluded that interactive e-books for production unit courses were valid, practical and effective to be used as teaching materials in production unit courses at the university level.